Identification of immunogenic epitopes for design vaccines against Leishmania spp. in dogs: sistematic review - Pádua, Josiane Aparecida Martiniano de (2022)
Visceral Leishmaniasis is a zoonotic disease that affects several species of mammals, including dogs, considered the main reservoirs in the urban environment. For the control and prevention of the disease in dogs, vaccination is considered a good measure. The objective of the present paper was to identify protective epitopes against protozoa of the genus Leishmania, in domestic dogs (Canis lupus familiaris), through bioinformatics tools, with initial antigen searches in scientific articles, grouped in a systematic review and the public database TriTrypDB: Kinetoplastid genomics Resource, with subsequent analyzes of T and B cell epitopes in Immune epitope Database and Analysis Resource, (IEDB), in which the search was limited using filters, to determine the genetic sequences of the peptides, which can be used later in the production of an effective recombinant vaccine against canine visceral leishmaniasis. As main results, it is worth noting the significant efficacy rates achieved by second and third-generation vaccines antigens. The excreted/secreted antigens of L. infantum and the LACK antigen showed considerable protection against Canine Visceral Leishmaniasis, the latter having also achieved protection against L. infatum infection. However, for the preparation of a new multiepitope vaccine, LiESp could not be considered and therefore, only the LACK and A2 antigens were classified to obtain data from the TriTrypDB and IEDB. A2 antigens, despite not showing significant protection, showed scientific relevance in the literature. It is possible to conclude that these antigens can be considered for the development of the new vaccine, as they are relevant in terms of efficacy rates, however, further analyses of their epitopes are necessary to fulfill this objective, because, for the development of an immunogen from these molecules, it is necessary to infer characteristics such as genetic sequence, length, molecular weight, antigenicity, and several others, to select the best epitopes and the best way to fuse them into a new antigen.